Homes of Taste : Economical Hints - Panton, J. E. (Cambridge library collection. British and Irish History, 19th Century, 1890)
Jane Ellen Panton (1847–1923) was the second daughter of the artist William Powell Frith, and a journalist and author on domestic issues. First published in 1890, this was one of a series of advice guides written by Panton on life and work in the middle-class home. With each chapter focusing on a different area of the house, the book offers advice to young married couples on how to make their homes 'tasteful without undue expense' by devoting time and effort to renovation and furnishing, and by choosing decorative styles that would not date. The author encourages her readers to become 'house proud', and to this end suggests that men should learn basic carpentry and refurbishment skills, while women should become proficient in needlework, as opposed to 'dawdling' over 'mere society flutter'. Providing a revealing snapshot of life in late nineteenth-century England, this book will appeal to historians and sociologists